The Importance of English Language Skills for University Students - Ahmad Sunandar; Bunga Citra Lestari; Dyah Ayu Kumala; Rona Imtiyaz; Sabrina Mutiara Az Zahra; Yaskia Mayrissa Maditta; Yosefa Maria Wellarana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
English is now a key language used in learning, research, technology, and talking across the world. So, being good at English is a key skill that university students need to succeed in their studies and future careers. This article looks at and brings together past research on why having good English skills is important for university students, especially when it comes to their success in school, getting a job, and being able to work well with people from different parts of the world. This study used a qualitative method by reviewing existing literature. Data were gathered from academic sources like peer-reviewed journal articles, books, and other scholarly publications between 2020 and 2025.These sources were found in databases such as Google Scholar, Scopus, ERIC, ScienceDirect, and SpringerLink. The results show that being good at English helps students do better in school, makes it easier to get a job, allows them to access scientific materials from around the world, and improves their ability to communicate and understand global issues. This review ends by saying that knowing the English language is an important skill that helps university students deal with the challenges of globalization and digital changes. So, colleges and universities need to focus more on teaching English to help students compete better in the global job market.